Relationship between socioeconomic conditions and the profile of self-care of the elderly University of Maturity of the Federal University of Tocantins (Research, Society and Development, 2022)
This study aims to verify the relationship between self-care and socioeconomic issues of the elderly in a Lifelong Learning program at the Federal University of Tocantins, in addition to demonstrating the results of health education interventions using pre-test and post-test. with the application of the ASA-A questionnaire. This is a cross-sectional, descriptive study with a quantitative approach carried out with 38 elderly people enrolled in the aforementioned program located in the city of Palmas-TO, aged between 60 and 75 years. As research results, it was identified that there were few changes from pre to post test with regard to self-care related to sharing personal items, since the elderly understand that there may be risks of contamination by biological agents such as viruses; as for the concern with oral health, most were aware of the risks of developing cavities or bacterial plaques and if there is no care with the mouth and maintenance of healthy practice, such as periodic brushing and flossing. As for the socioeconomic conditions of the participants, the results were very similar to other studies carried out in Brazil, demonstrating that the minimum financial conditions can affect self-care, which can generate mental and social losses and directly affect the autonomy of the elderly. It is concluded that there is a need to continue with educational actions for the elderly at the University of Maturity, since the actions have positive results in terms of self-care, but that it is also necessary to understand that the limitations imposed by aging, such as the socioeconomic conditions and low education, which are considered challenges faced by the elderly population.